2016
DOI: 10.1177/1354067x16655459
|View full text |Cite
|
Sign up to set email alerts
|

Rekindling individualism, consuming emotions: Constructing “psytizens” in the age of happiness

Abstract: Happiness has become a new moral regime in neoliberal societies that defines what is right and wrong and stresses the insource of responsibility. More importantly, happiness stands out as a new model of selfhood that aligns with the neoliberal ideology of individualism and consumerism at the same time that legitimizes and rekindles this same ideology in seemingly nonideological terms through the discourse of science. The paper claims that this model of selfhood turns citizens into psytizens, that is, into psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 35 publications
1
20
0
4
Order By: Relevance
“…56 It is important to be wary though of how neoliberal ideas could turn resilience building into a project of the self, with a focus on individual choice and the pursuit of individual wellbeing, while neglecting the systemic realities facing GPs in the NHS. 50,62…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…56 It is important to be wary though of how neoliberal ideas could turn resilience building into a project of the self, with a focus on individual choice and the pursuit of individual wellbeing, while neglecting the systemic realities facing GPs in the NHS. 50,62…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The NHS as a 'marketplace' places a limit on quality of care. 49 Previous research has found that neoliberal ideas encourage a 'specific way of being, acting, and understanding the world, which is highly individualistic'; 50 the authors found that NHS marketisation promotes a kind of GP individualism -or atomisation -where GPs feel increasingly removed from meaningful interactions with patients and colleagues, even loved ones. Although some doctors cope better in the new NHS than others, 51 there is a growing recognition that primary care is at breaking point.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Continuing and developing this line of thought, sociologists argue that in late modernity, while other identity anchors, such as religion and community, have lost some of their grounding, work has become “a main center of identity” (Beck, 2001, p. 268). Moreover, in neoliberal societies, citizenship is being gradually narrowed down to its economic component alone, based on the ability of the individual to support herself financially (Cabanas, 2016; Kessler-Harris, 2003; Sa’ar, 2016), thus increasing the centrality of work as a marker of “character” (Sennett, 1998).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Neoliberalism is not some clever plot to rule the world. It is, by definition, an impudent, generalised refusal to plot or plan anything beyond one's own immediate 'well-being' (Scharff 2016;Cabanas 2016).…”
Section: Periodising Neoliberalismmentioning
confidence: 99%